AMAL AHLU AL-MADINAH SEBAGAI SUMBER HUKUM ISLAM (Pandangan Imam Malik Ibn Anas dalam Kitab Al-Muwatta`) - Najib, Agus Moh. (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Imam Malik ibn Anas (93-175 H/711-791 M) considers that the practice is well established in Medina (amal Ahlu al-Madi>nah) are a source of law to be followed. Amal Ahlu al-Madi>nah according to Imam Malik is a source of law that must be obeyed and there should not menyelisihi. The reason is because Medina is the city where the Prophet's Hijrah, where most of the Qur'an was revealed and the halal and haram set. Medina resident is a resident of the companions who witnessed the revelation down and obey all that is commanded by the Prophet, so they are the ones most aware of the purpose of revelation and the Sunnah of the Prophet. This statement is as he wrote in his masterpiecenya, the Kitab Al-Muwatta '. Imam Malik's view is a reaction of some scholars, such as Al-Lays, Imam Shafi'i and Al-Syaibani. Among scholars Malikiyah, differentiation occurs in the category of charity ahlu al-medina, which is based on history and based on ijtihad. They agreed to accept the first of its kind and different opinions for the latter kind. If we look closely, Amal Ahlu al-Madi>nah raised Imam Malik in Al-Muwatta 'is not always rely on the traditions of the Prophet, but many do not have any rest, good traditions of the Prophet, words and sayings tabi'in friends. Imam Malik prioritize amal Ahlu al-Madi>nah of the ahad hadith and the opinions of friends and tabi'in. Viewed politically, the view of Imam Malik is also a form of opposition to the ruler at that time, the Abbasid dynasty, by clarifying the authority of Madinah through the concept of amal Ahlu al-Madi>nah.